Granular sample collection simulation via counter rotating wheels sampler for small-sized system at reduced gravity environment - Sitepu, Elioenai; Cullen, David C. (Elsevier, 2023)
The launching and planning of space missions for asteroid exploration have increased due to their scientific interest and potential resources for future use, such as composition analysis and In-Situ Resource Utilization (ISRU) demonstration. Furthermore, the design of sample acquisition systems has been limited to accommodate CubeSats or small-sized payloads, as the utilization of CubeSats for scientific missions is also on the rise. Therefore, sample collection is a critical step in preparing for these missions. The focus of this study is to analyse a conventional counter rotating wheels sample acquisition concept on a granular bed in microgravity conditions on an asteroid, as well as on the Moon and Mars with different gravitational forces. The study introduces a set of Archimedes screws into the wheels as a novel sample acquisition approach and utilizes Discrete Element Modelling (DEM) to analyse it. The simulation shows that the addition of an Archimedes screw sampler is more efficient in collecting samples in a short sampling time (<2 s) than a conventional counter rotating wheels. For implementation on planetary bodies with significant gravitational force, such as the Moon or Mars, a limitation is observed and redesigning the sample collection chamber might be necessary to capture the particles. Finally, the study highlights potential future work that could provide a more detailed and comprehensive understanding of the newly designed counter rotating wheels sampler.
Keywords: Sample acquisition system; In-situ resource utilization; Small-sized payload; Microgravity; Granular behaviour; Counter rotating wheels